2008
DOI: 10.1136/jnnp.2008.144667
|View full text |Cite
|
Sign up to set email alerts
|

Increasing prevalence and incidence of multiple sclerosis in South East Wales

Abstract: Recent change in disease incidence and prevalence in this population is likely to be the result of environmental factors that have been operative in the past few decades in women alone and infers avoidable risk factors. Modelling of current overall incidence suggests a further increase in prevalence to 260 per 100 000 population within the next 20-40 years. Further studies are needed in order to identify recent changes in sex specific environment and lifestyle that confer susceptibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
92
3
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(115 citation statements)
references
References 21 publications
16
92
3
3
Order By: Relevance
“…Our data showing an increasing prevalence over a period of decades is consistent with several studies conducted in the northern hemisphere [6,7,8,9] and in another southern hemispheric country, Australia [10,11,12,13]. Repeated surveys in several Australian cities including Perth, Newcastle and Hobart, Tasmania, have shown increases in MS prevalence between 1951 and 2009 [10,11,12,13].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our data showing an increasing prevalence over a period of decades is consistent with several studies conducted in the northern hemisphere [6,7,8,9] and in another southern hemispheric country, Australia [10,11,12,13]. Repeated surveys in several Australian cities including Perth, Newcastle and Hobart, Tasmania, have shown increases in MS prevalence between 1951 and 2009 [10,11,12,13].…”
Section: Discussionsupporting
confidence: 78%
“…A number of studies [6,7,8,9] on the prevalence and incidence of MS in the northern hemisphere suggest a steady rise in the absolute number of cases identified. In the southern hemisphere, repeated surveys in the previously surveyed regions of Australia [10,11,12,13] have also shown a consistent trend of increasing prevalence and incidence of MS over time.…”
Section: Introductionmentioning
confidence: 99%
“…Other explanatory factors for an increasing MS incidence are largely unknown but changes in environmental factors have been suggested [28,29]. In line with our study, several other studies reported that the increasing MS incidence was mostly attributable to an increase among women [23,25,27,30,31,32,33,34]. Solid evidence for the shift in F:M sex ratio is yet unknown but perhaps changing lifestyle factors among women, e.g.…”
Section: Discussionsupporting
confidence: 82%
“…Recent estimates put the sex ratio between ϳ3:1 (28) and ϳ5:1 (30), depending on the decade of birth. An increase in the female bias of MS has been observed in the United States (26,77), Canada (28,30), Australia (78), the United Kingdom (29,79), Norway (27,80), and Sardinia (81), due to an increased incidence among women, rather than to a decreased incidence among men. One explanation for the female bias could be X-linked risk factors, but extensive X chromosome linkage studies have not revealed MS susceptibility loci (82), and the rapidity of the femaleto-male sex ratio increase argues against a genetic origin (28).…”
Section: Discussionmentioning
confidence: 99%